Mechanically robust all-hydrogel supercapacitor having seamless interfaces among components by rapid phase transition of physical gels - Kim, Jong Sik; Park, Jin Hyeok; Hwang, Jongkook; Shim, Tae Soup (Chemical Engineering Journal, 2023)
In a flexible energy storage device, the interface between the components not only degrades the electrochemical performance but also makes it mechanically vulnerable. Therefore, interface engineering is important to ensure device performance. Here, we propose a design strategy for the fabrication of seamless energy storage device that maximizes the structural integrity between all-components. Utilizing a rapid phase transition characteristic of agarose, a seamless device composed of carbon cloth, agarose/activated carbon electrode, and agarose electrolyte were prepared. The seamless interface improved areal capacitance and lap-shear strength by 35% (166.6 mF/cm2) and 1000% (12 kPa), respectively, compared to that of the conventional sandwich-type supercapacitor. In addition, the impedance of the seamless device was measured as 80% of that of the sandwich device demonstrating a decrease of interfacial resistance. While the areal capacitance of the seamless device was maintained even after 100 bending cycles, the device failure by interfacial slip for the sandwich device was observed. Considering that flexible electronic devices are subjected to repeated mechanical deformations, the device fabrication strategy using phase changing materials proved to be very effective which can be applied to versatile applications.
Keywords: Agarose; All-hydrogel supercapacitor; Flexible supercapacitor; Interface engineering; Phase changing materials; Physical gel; Quasi-solid electrolyte; Rapid phase transitions; Sandwich devices; Seamless interfaces; All-hydrogel supercapacitor; Flexible supercapacitor; Interface engineering; Phase changing materials; Physical gels; Quasi-solid electrolytes